The Successful Ghana Election of 2008 – a Convenient Myth? Ethnicity in Ghana's Elections Revisited - Heinz Jockers; Dirk Kohnert; Paul Nugent (German Institute of Global and Area Studies (GIGA), 2009)
Ghana's 2008 elections have been hailed by national and international observers as a model for Africa. This perception has prevailed despite persistent concerns about 'ethnic block voting' and electoral fraud. Electoral malpractice and vote rigging along ethnic lines in Ghana's virtual two-party system could regain decisive importance as a 'third force' that could tip the balance in future, possibly coming to represent an even more important factor than the smaller opposition parties. Unfortunate diplomatic and technocratic biases in election monitoring, combined with a reluctance on the part of the responsible authorities to investigate irregularities in what appears to be a long history of fraudulent 'ethnic block voting', amounts to a dangerous time bomb of unresolved conflict which could explode in future elections. – – Die erfolgreichen Wahlen in Ghana 2008 - ein zweckdienlicher Mythos? Die Rolle von Ethnizität bei den Wahlen in Ghana wird erneut diskutiert. Die Wahlen in Ghana 2008 werden von nationalen und internationalen Beobachtern als ein Vorbild für Afrika gelobt. Diese Auffassung steht im Gegensatz zur anhaltenden Besorgnis wegen Stimmenabgabe en bloc und Wahlbetrug. Auf Ethnizität zurückzuführende Wahlfälschung kann im faktischen Zwei-Parteien-System Ghanas als Zünglein an der Waage eine größere Bedeutung als 'dritte Kraft' gewinnen als die kleineren Oppositionsparteien. Bedauerliche diplomatische und technokratische Einseitigkeit bei der Wahlbeobachtung, kombiniert mit der Scheu verantwortlicher Behörden vor einer Untersuchung vermutlich jahrelang praktizierter ethnischer Blockabstimmung und jahrelangen Wahlbetrugs, bilden eine gefährliche Zeitbombe ungelöster Konflikte, die in künftigen Wahlen explodieren könnte.
Keywords: D72; N47; Z1; 300; elections; ethnicity; election observation; informal institutions; impunity; Ghana